Cell-secreted Flavins Bound to Membrane Cytochromes Dictate Electron Transfer Reactions to Surfaces with Diverse Charge and pH - Okamoto, Akihiro (Nature Publishing Group, 2014)
The variety of solid surfaces to and from which microbes can deliver electrons by extracellular electron transport (EET) processes via outer-membrane c-type cytochromes (OM c-Cyts) expands the importance of microbial respiration in natural environments and industrial applications. Here, we demonstrate that the bifurcated EET pathway of OM c-Cyts sustains the diversity of the EET surface in Shewanella oneidensis MR-1 via specific binding with cell-secreted flavin mononucleotide (FMN) and riboflavin (RF). Microbial current production and whole-cell differential pulse voltammetry revealed that RF and FMN enhance EET as bound cofactors in a similar manner. Conversely, FMN and RF were clearly differentiated in the EET enhancement by gene-deletion of OM c-Cyts and the dependency of the electrode potential and pH. These results indicate that RF and FMN have specific binding sites in OM c-Cyts and highlight the potential roles of these flavin-cytochrome complexes in controlling the rate of electron transfer to surfaces with diverse potential and pH.